GLACIAL TURBIDITE SHELF DEPOSITS - Lavrushin Y.A.; Chistyakova I.A. (My University, 1988)
Recent surveys of bottom sediments in the Barents Sea revealed deposits of an unusual kind, whose genesis was attributed to processes of submarine slumping and suspension flow. The clayey sediments classified as suspension-flow deposits proper are dark-gray silts with a cyclic structure containing numerous lumps of compact dark-gray silt. The origin of such deposits was attributed to periodic downslope sliding of sediment into the central part of the basin as a result of the tectonic instability of its floor, especially in fault zones. Our investigations in the Barnets Sea have shown that sediments which can be classified as turbidites are distributed here locally, but fairly extensively.